INDONESIAN GREEN TAXONOMY AND SUSTAINABLE FINANCING GOVERNANCE: A LEGAL ANALYSIS OF THE SUSTAINABILITY REPORT OF BANK SYARIAH INDONESIA LIMITED COMPANY - Hidayah Ken Kinasih; Wardah Yuspin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Economic development focused solely on financial gain has triggered various environmental damages. In response to this problem, the banking sector is now required to implement sustainable financing principles. Unlike previous studies that generally only discuss sustainable finance descriptively, this article's novelty lies in the development of integrated compliance parameters—based on the Green Taxonomy, POJK No. 51/POJK.03/2017, IFRS S1/S2, and Maqashid Syariah—to critically assess the risk of greenwashing in Islamic banks. This study aims to analyze the Indonesian Green Taxonomy criteria as a banking governance standard and to examine the conformity of Bank Syariah Indonesia Limited Company’s (BSI) Sustainability Report to these guidelines. Using a normative juridical approach, this study finds that BSI has a dual responsibility: compliance with state regulations (POJK No. 51/POJK.03/2017) and compliance with the principles of environmental preservation in Islam (Hifz al-Bi'ah). The results of the study indicate that compliance with the Green Taxonomy instrument is very important to prevent the practice of manipulating environmentally friendly images (greenwashing), so that the distribution of bank funds is proven to be in line with the constitutional mandate and human responsibility to protect the earth.